1993
DOI: 10.2466/pr0.1993.73.3f.1251
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hypnotic Susceptibility via a Phenomenological Approach

Abstract: The hypnotic susceptibility of 300 nursing students was predicted via an instrument called the Phenomenology of Consciousness Inventory. The students experienced the Harvard Group Scale of Hypnotic Susceptibility and subsequently completed the self-report inventory with reference to their experience of hypnosis. Regression analyses generated a multiple R of .67 between subjects' susceptibility, as measured by the Harvard scale, and their predicted susceptibility, based on the (sub)dimensions of the inventory. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 9 publications
0
20
2
Order By: Relevance
“…It has been shown to be of appropriate predictive (Pekala & Kumar, 1984, 1987Forbes & Pekala, 1993;Hand, Pekala, & Kumar, 1995), and discriminant (Pekala & Kumar, 1986, 1989Pekala, Forbes, & Contrisciani, 1989) validity (Pekala, 1991b).2…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown to be of appropriate predictive (Pekala & Kumar, 1984, 1987Forbes & Pekala, 1993;Hand, Pekala, & Kumar, 1995), and discriminant (Pekala & Kumar, 1986, 1989Pekala, Forbes, & Contrisciani, 1989) validity (Pekala, 1991b).2…”
Section: Methodsmentioning
confidence: 98%
“…The pHGS score is based on a regression equation using 10 (sub)dimensions of the PCI. Three research studies have generated validity coefficients of about .60 between the subjects' actual Harvard Group Scale scores and their predicted Harvard Group Scale (pHGS)scores (Pekala,& Kumar, 1984, 1987Forbes & Pekala, 1993). Anadditional study (Hand, Pekala, & Kumar, 1995) found a Pearson rof .86 between pHGS scores and the Stanford, Form C. Predicted Harvard Group Scale (pHGS) scores have been found helpful (Pekala, 1995b) in screening subjects prior to treatment plan development and implementation, and provides a depth 214 PEKALA AND FORBES level of trance that appears to correlate with how helpful hypnosis may be in treatment.…”
Section: Prior Research: Regression Analysis Studiesmentioning
confidence: 99%
“…Although there may be different types of trance (possibly based on individual differences factors and dependent on the qualitative nature of that trance), there may at the same time be some commonality across these different types of trance, analogous to Spearman's (1904Spearman's ( , 1923 "g" factor for general mental ability, vis-à-vis different types of intelligence, a la Gardner (1983). (Pekala & Kumar, 2000, p. 111) Downloaded by [University of Waikato] at 12:36 10 July 2014 Pekala Based on regression analyses using the PCI (sub)dimensions to predict the total scale score from the Harvard, we generated a predicted Harvard Group Scale (pHGS) score (Forbes & Pekala, 1993;Pekala & Kumar, 19841987) which correlated about .60 with the actual total Harvard Group Scale scores. As we wrote 20 years ago (Pekala & Nagler, 1989), we thought it premature to label the state associated with a high pHGS score a "hypnotic" state, because we did not know if experiencing all the phenomenological parameters that would generate a high pHGS score would be associated with hypnotic effects.…”
Section: The Methodologymentioning
confidence: 99%
“…A methodology has been developed and presented in the literature (Forbes & Pekala, 1993;Pekala, 1991bPekala, , 2002Pekala & Kumar, 1984, 1987, 2007 that allows for concepts like hypnosis or trance to be defined and estimated. 3 To estimate "hypnotic trance" or what Weitzenhoffer (2002) has called "hypnosis," a phenomenological measure called the hypnoidal state score, also known as the predicted Harvard Group Scale (pHGS) score, was defined and developed:…”
Section: The Methodologymentioning
confidence: 99%
“…The HS score operationalizes hypnotic depth in terms of a linear combination of ratings on 10 PCI dimensions, and ranges between 1 and 9 (see, Pekala, 1991a;Pekala & Kumar, 2000;Pekala & Kumar, 2007;Pekala, Kumar, Maurer, Elliott, & Moon, 2006;Pekala & Nagler, 1989). HS scores correlate at about .60 with HGSHS: A objective scores (Forbes & Pekala, 1993;Pekala & Kumar, 1984;Pekala & Kumar, 1987).…”
Section: Post-suggestion Measuresmentioning
confidence: 99%